VectorNet Data Series 3: Culicoides Abundance Distribution Models for Europe and Surrounding Regions. (16th September 2020) - Balenghien, Thomas; Alexander, Neil; Arnþórsdóttir, Auður Lilja; Bisia, Marina; Blackwell, Alison; Bødker, René; Bourquia, Maria; Boutsini, Sofia; Carpenter, Simon; Colenutt, Claire; Culverwell, Lorna; Cvetkovikj, Aleksandar; et al.
This is the third in a planned series of data papers presenting modelled vector distributions produced during the ECDC and EFSA funded VectorNet project. The data package presented here includes those Culicoides vectors species first modelled in 2015 as part of the VectorNet gap analysis work namely C. imicola, C. obsoletus, C. scoticus, C. dewulfi, C. chiopterus, C. pulicaris, C. lupicaris, C. punctatus, and C. newsteadi . The known distributions of these species within the Project area (Europe, the Mediterranean Basin, North Africa, and Eurasia) are currently incomplete to a greater or lesser degree. The models are designed to fill the gaps with predicted distributions, to provide a) first indication of vector species distributions across the project geographical extent, and b) assistance in targeting surveys to collect distribution data for those areas with no field validated information. The models are based on input data from light trap surveillance of adult Culicoides across continental Europe and surrounding regions (71.8°N –33.5°S, – 11.2°W – 62°E), concentrated in Western countries, supplemented by transect samples in eastern and northern Europe. Data from central EU are relatively sparse.